P53 is the strongest predictor of survival in high-risk primary breast cancer patients undergoing high-dose chemotherapy with autologous blood stem cell support - Hensel, Manfred; Schneeweiss, Andreas; Sinn, Peter; Egerer, Gerlinde; Solomayer, Erich-Franz; Haas, Rainer; Bastert, Gunther; Ho, Anthony Dick (International journal of cancer, 2002)
Our purpose was to determine the predictive value of tumor biologic parameters in patients with HRPBC who received HDCT with ASCT as first-line treatment. From September 1992 to May 2000, 149 stage II or III HRPBC patients were enrolled in a single-arm trial using a tandem HDCT regimen followed by ASCT. Her2/neu, p53, Ki67 and bcl-2 protein expression was studied using immunohistochemic staining on formalin-fixed, paraffin-embedded primary tumor sections. DNA content of tumor cells (DNA index) and tumor cell proliferation (SPF) were measured by DNA flow cytometry. The relationship between these tumor biologic parameters, on the one hand, and DFS, DDFS and OS, on the other, was analyzed. With a median follow-up of 43 months (range 7-106), p53 protein accumulation (p = 0.000004), negative combined hormone receptor status (p = 0.003) and Her2/neu overexpression (p = 0.02) were significant negative predictors of OS in univariate analysis. A poorer DFS was associated with p53 positivity (p = 0.04) and nodal ratio ≥0.8 (p = 0.008). Poorer DDFS was associated with p53 positivity (p = 0.03). In multivariate analysis, Her2/neu overexpression (RR = 3.86, 95% CI 1.48-10.1, p = 0.006) and p53 overexpression (RR = 6.06, 95% CI 2.22-16.52, p < 0.001) proved to be independent predictors of adverse OS. p53 overexpression was the only independent predictor of DFS (RR = 2.21, 95% CI 1.07-4.57, p = 0.03). p53 overexpression and Her2/neu overexpression are independent negative predictors of survival in HRPBC treated with HDCT. The adverse impact of these biologic features was probably not altered by HDCT. For HRPBC patients with tumors not overexpressing Her2/neu or p53, HDCT may be an appropriate approach to achieve long-term survival and tumor control. © 2002 Wiley-Liss, Inc.